Variation in address practices across languages and nations. A comparative study of doctors’ use of address forms in medical consultations in Sweden and Finland - Camilla Wide; Hanna Lappalainen; Anu Rouhikoski; Catrin Norrby; Camilla Lindholm; Jan Lindström; Jenny Nilsson (John Benjamins Publishing Company, 2022)
This article compares variation in the use of address practices across languages (Swedish, Finnish) and national varieties (Sweden Swedish, Finland Swedish). It undertakes quantitative and qualitative analyses of three sets of transcribed medical consultations. In Sweden Swedish, address pronouns which lower social distance overwhelmingly dominate. In Finnish, both address forms reducing social distance and practices maintaining greater distance are found, with age and level of acquaintance revealed as the most salient factors. Finland Swedish is located somewhere between Sweden Swedish and Finnish, displaying a stronger tendency than Finnish to use informal direct address forms to reduce social distance, but also showing similarities with Finnish in the use of direct formal address and indirect address. The differences can be related to larger socio-cultural patterns which, however, form a continuum rather than a fixed set keeping the two languages and countries completely apart.